Territory, city and politics in venezuela. future alternatives in the vertex of modernity and crisis (2008)
The article looks to demonstrate that the model of urbanization and the configuration of the historically consolidated territory in Venezuela are totally unfair and not sustainable in social and environmental terms. The results of the referendum to approve a constitutional reform in 2007 illustrate an unsolvable social-territorial conflict beyond the narrow margin in the difference of votes that lean the balance towards the rejection to the Reformation. This means that the main vortexes of the discussion will continue demanding great doses of innovation to solve the social-territorial conflict resulting from the relations between capitalist city and socialist city; concentration versus decentralization of the population; system of cities or primacy of the capital; urbanization or countryside predominance, regional reconfiguration and territorial integrity; modernity or “post-metropolitan transition”, “to be politician” and “to be citizen”, among others. It is also analyzed what did the project of constitutional reform meant related to the idea of vindication of the city and the citizenship emergency as maximum expressions of collective patrimony and universal dynamics to the social and space forms of coexistence that humankind recognized and adopted definitively at the last years of the twentieth century.